The Economics of Regional Demarcation in Banking - Simone Raab; Peter Welzel (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2010)
Cooperation among savings and cooperative banks was criticized by the European Commission because of potentially anti-competitive effects. In an industrial economics model of banks taking deposits and giving loans we look at regional demarcation as one of such cooperative practices. There are two adjacent markets with one savings or cooperative bank being focused on each one and one private commercial bank serving both. We find that abolishing regional demarcation indeed increases total loan volume. Savings or cooperative banks always improve market performance and do better without regional demarcation which shields the private commercial bank from aggressive competition by these banks.
Keywords: G21; L41; L44; L33; L13; 330; banking; competition; cooperation; non-profit firms; Bank; Wettbewerb; Sparkasse; Kreditgenossenschaft; Regionalbank; Unternehmenskooperation; Industrieökonomik; Theorie; Deutschland